Idiopathic Localized Involutional Lipoatrophy Responsive to Injection Normal Saline: A Case Series - Prashansa Jaiswal; Aishwarya Dua; Shilpi Shloka; Aaditya Sirohi (Wolters Kluwer Medknow Publications, 2024)
Background: Localized involutional lipoatrophy (LIL) is a rare distinctive idiopathic form of localized lipoatrophy. It is characterized by loss of adipose tissue without antecedent inflammation and was first described by Peters and Winkelmann in 1986. There have been only a few reports on LIL in the English literature. We, herein, report cases series of idiopathic LIL (ILIL) and determine the efficacy of injection normal saline in such patients. Objectives: The aim of the study was (1) to study the clinical features and evolution of lesions in patients diagnosed with ILIL and (2) to determine the efficacy of injection normal saline in such patients. Materials and Methods: It was a retrospective study conducted in the department of dermatology at a tertiary care center from May 2021 to April 2023. We included all clinically suspected cases of ILIL with characteristic histopathological findings who were treated with injection normal saline. All cases with history of antecedent injections, vaccination, or medications before the development of lesion were excluded from the study. Results: The median age of presentation was 3 years. Ten (71%) patients were male, while 4 (29%) were female. All patients had lesion on buttocks and all were unilateral. Overall, 10/14 (71%) patients responded to the treatment. Conclusions: This report demonstrates that serial saline injections provide a safe, relatively rapid, cost-effective, and uncomplicated solution to idiopathic involutional lipoatrophy.